Multimodal optical imaging and genetic features of AB variant GM2 gangliosidosis: a case report - Chen, Qin; Lu, Fang (Frontiers in Pediatrics, 2023)
Background AB variant GM2 gangliosidosis is an extremely rare autosomal recessive lysosomal storage disease. Macular cherry-red spots are the most commonly described ocular sign in this disease. Here, for the first time we report a case of an infant with AB variant GM2 gangliosidosis, along with multimodal optical imaging and genetic testing results. Case description A 7-month-old Chinese girl presented to the hospital with nystagmus for 2 months. Her family history for this condition showed negative results, and her parents were not known to be consanguineous. Fundus photography showed a cherry-red spot with a ring of whitish infiltrate surrounding both macula. Fundus fluorescein angiography showed normal retinal circulation and vessels. Optical coherence tomography (OCT) revealed a thickening and increased reflectivity of the inner retinal layers with a shadowing effect on the outer structures. The patient had no obvious neurological symptoms, and the MRI results of the head were normal. The whole-exome genome sequencing results showed that there was a homozygous deletion (chr5: 150639196-150639548) of exon 2 in the GM2A gene. Finally, the patient was diagnosed with AB variant GM2 gangliosidosis. Conclusions AB variant GM2 gangliosidosis is a rare disease affecting multiple nervous systems. Before the occurrence of typical neurological symptoms, the clinical features of fundus photography and OCT help us diagnose GM2 gangliosidosis.